2008
DOI: 10.1016/j.seizure.2007.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term levetiracetam treatment affects reproductive endocrine function in female Wistar rats

Abstract: Our findings indicate a possible effect of LEV on the hypothalamic-pituitary-gonadal (HPG) axis and ovarian morphology in non-epileptic rats. The effects differ from those previously described for other AEDs. Caution must be taken before these results can be applied to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
2
27
1
Order By: Relevance
“…If a child responded to LEV in the ICU, had no adverse effects noted acutely, and had an indication for additional anticonvulsant therapy, continuing LEV would be a reasonable choice (38). However, recent data have demonstrated that while generally superior to older anticonvulsants in terms of adverse events, newer anticonvulsants are also associated with long-term effects (39) including behavior changes (40, 41) in humans and endocrine (42) and bone growth effects in animals (43). As further data emerge comparing the newer anticonvulsants for long-term use, decisions regarding appropriate anticonvulsants for acute use in an ICU setting and prolonged use in an outpatient setting may need to be separated.…”
Section: Discussionmentioning
confidence: 99%
“…If a child responded to LEV in the ICU, had no adverse effects noted acutely, and had an indication for additional anticonvulsant therapy, continuing LEV would be a reasonable choice (38). However, recent data have demonstrated that while generally superior to older anticonvulsants in terms of adverse events, newer anticonvulsants are also associated with long-term effects (39) including behavior changes (40, 41) in humans and endocrine (42) and bone growth effects in animals (43). As further data emerge comparing the newer anticonvulsants for long-term use, decisions regarding appropriate anticonvulsants for acute use in an ICU setting and prolonged use in an outpatient setting may need to be separated.…”
Section: Discussionmentioning
confidence: 99%
“…Administration duration of LEV was chosen according to the completion time of spermatogenesis and was in accordance with the guideline OECD 416: Guideline For Testing of Chemicals: Two-Generation Reproduction Toxicity Study [12], and doses of LEV were determined according to previous studies [1315]. Also, the therapeutic doses of LEV were between 500 mg/day and 3000 mg/day [11] and the doses we have chosen were in accordance with the guidelines extrapolating human doses to animal doses [16].…”
Section: Methodsmentioning
confidence: 99%
“…Low-dose LEV was found to impair longitudinal skeletal growth and increase the risk of fractures in immature rats [140]. LEV was found to affect serum estradiol levels, suggesting that young and female individuals might be at risk of fractures with long-term use of LEV [141]. However, other reports [142,143] did not observe this effect.…”
Section: New Generation Aedsmentioning
confidence: 99%